Akselerasi Daya Saing Produk Rumput Laut melalui Transformasi Digital Pemasaran Berbasis Platform Online - Hidayat, Andi Ircham; Askar, Hardianty; Akhmad, Nur Fahmi (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Limited digital literacy and restricted access to online marketing have resulted in seaweed products in Bontojai Subdistrict, Bantaeng Regency, being marketed conventionally, with a narrow reach and low added value. This community engagement initiative aims to accelerate product competitiveness through the digital transformation of marketing, utilising online platforms such as e-commerce, social media, and messaging applications. A Participatory Action Research (PAR) approach was employed, encompassing stages of planning, training implementation, practical mentoring, observation, and evaluation. The results indicate an improvement in digital marketing literacy, an increase in the number of business actors with active marketplace accounts, and a broader reach of online promotional activities. This transformation has facilitated expanded market access and enhanced the added value of seaweed products. Participatory-based intervention has proven to be an effective model for empowering the digital economy of coastal communities.